Latihan Penguatan pada Rehabilitasi Penyakit Paru Obstruktif Kronik: Proses Sistemik dan Biomolekuler - Ferius Soewito (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2019)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a global health problem that frequently result in disability. Disability can be caused not only by COPD effect on lung, but also it’s systemic effect. One of the effect is on the skeletal muscle. Strength training is one og rehabilitation method that effective in maintaining functional capacity of COPD patient. This review discuss systemic and biomolecular aspect of COPD, strength training and how strength treaining can affect functional capacity of COPD patient.